Ergonomic working positions with musculoskeletal disorders and work fatigue in lifting workers at a furniture company - Sunarsieh, Sunarsieh; Paulina, Paulina; Rahmawati, Indah Nurdiana Setya (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Furniture workers who lift and carry heavy loads face various ergonomic risks that impact their work performance and health. Field observations indicate that manual material handling is carried out conventionally with heavy and large loads without the use of assistive devices. This results in workers working in non-ergonomic positions. In addition, the high frequency of repetitive movements and the lack of education on correct lifting techniques increase the risk of fatigue and musculoskeletal disorders. Objective: This study aims to analyze the differences in work fatigue and musculoskeletal disorders in the ergonomic work positions of furniture workers. Methods: The study subjects were 60 male workers. Work fatigue was measured using a reaction time meter with millimeter (mm) units and a questionnaire. This study used an experimental design with a randomized controlled trial method. Data collection on musculoskeletal disorders used the Nordic Body Map (NBM) questionnaire. Results: Comparison of pre-employment and post-employment scores in the treatment group showed that the average value decreased from 719.63 mm before work to 235.07 mm after work. The average musculoskeletal disorders in the control group increased before and after work from 30.30 to 33.30 (p=0.001). These results indicate that ergonomic work position interventions can reduce fatigue and musculoskeletal disorders in lifters. Conclusion: Therefore, companies need to implement comprehensive work ergonomic standards including manual handling technique training for all workers, provision of lifting aids such as trolleys or hand trucks, and worker health monitoring as a preventive measure against work fatigue and musculoskeletal disorders.